KANDUNGAN ZAT BESI DAN KONSUMSI KUKIS UBI JALAR UNGU DENGAN RASIO TEPUNG TEMPE DAN TEPUNG UDANG REBON - Sandi Eka Putra; Netti Herawati; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this research were to find out the Iron content and purple sweet potato cookies consumption with ratio tempe flour and small shrimp flour which have high nutrition and meet the quality standard of cookies (SNI 01-2973-1992). This research used Complete Randomized Design (CRD) by 4 treatments and 4 replications. The treatments were K1 (tempe flour 20%, small shrimp flour 1%), K2 (tempe flour 15%,  small shrimp flour 6%), K3 (tempe flour 10%,  small shrimp flour 11 %), and K4 (tempe flour 5%,  small shrimp flour 16%). The results showed the treatments have the significant effect on the water, ash, protein, iron and cookies consumption. The average of cookies consumption on the whole children group ages 1-6 years was 9.34 pieces. The average of cookies consumption on the children group ages 1- 3 years was 8.82 pieces. The average of cookies consumption on the children group ages 4-6 years was 9.87 pieces. The chosen cookies was K2 which had water (2.33%), ash (1.88%), protein (12.54%) and iron (0.112%) had met the standard quality of cookies (SNI 01-2973-1992). Keywords: Cookies, purple sweet potato, tempe flour, small shrimp flour, cookies consumption.